Urgensi Penerapan Lembaga Dwangsom (Uang Paksa) Pada Perkara Hadhânah di Pengadilan Agama dalam Perspektif Maqâshid al-Syarî’ah - Huzaimah, Arne; Aziz, Syaiful (al-'adalah, 2018)
This article discusses the implemention of the forced money (dwangsom institution) in the hadhânah case in the Religious Courts from the perspective of maqâshid al-shariah. This study found that the application of dwangsom sentences for hadhânah cases is very important to be applied, especially to the defendant who objects to carrying out court decisions; or default to the agreement; or there will be difficulties at the time of execution; or the plaintiff suffers a loss. In addition, implementing dwangsom in the hadhânah case will pave the way for the benefit of children who are still in the process of growth even though their parents divorce. Therefore, even if not asked by the plaintiff, the judge himself can decide the dwangsom sentence to the defendant to ensure the fulfillment of the needs of the children.